Prognosis of primary aldosteronism achieved incomplete surgical remissionand changes in plasma aldosterone, plasma renin activity and biochemical indicators: changes in plasma aldosterone, plasma renin activity in primary aldosteronism - Zeng, Xiaoyong (Journal of Medical Biochemistry, 2025)
Background and Purpose: Some primary aldosteronism (PA) patients with spontaneous hypokalemia achieved incomplete remission after surgical treatment. In this study, we aim to construct a nomogram to predict surgical benefits for PA patients with typical symptoms, which may help doctors assess prognosis and develop treatment plans. Methods: This retrospective cohort study enrolled 162 patients between January 2017 and January 2024. Baseline characteristics, clinical indicators, and biochemical results were compared among patients with different clinical and biochemical outcomes. A nomogram was developed and internally validated with risk factors selected from univariate and multivariate logistic regression analyses. Results: Respectively, complete clinical and biochemical success was achieved in 69 patients (42.6%) and 129 patients (79.6%). Five risk factors for incomplete remission were used to develop a nomogram. The area under the receiver operating characteristic curve (AUC) was 0.856 (0.788-0.924) in the training dataset and 0.726 (0.580-0.872) in the validation dataset. The calibration curve showed good agreement, and the decision curve analysis demonstrated clinical utility of this model. Conclusions: PA patients with older age, higher systolic blood pressure, lower plasma aldosterone, more than 5 years of hypertension, and an adrenal gland mass on the left side or both sides had more probability to achieve incomplete remission after the surgery.